The Effect of Seven Developmental Care Models on Mothers' Stress and Premature Infants' Length of Hospitalization - Andi Fatmawati Syamsu; Fajrillah Kolomboy; Rizkaningsih Rizkaningsih (Poltekkes Kemenkes Palu, 2023)
The Neonatal Integrative Developmental Care Model (NIDCM) is a holistic model of premature infant care that refers to the seven neuroprotective developmental care cores involving the family. This study aimed to assess the effect of the application of NIDCM on mothers’ stress response and length of stay in the neonatal care unit. This study used quasi-experimental with nonequivalent control group pre and posttest design. This study was carried out in the neonatal care unit at RSUP Dr. Wahidin Sudirohusodo Makassar from January 2020 to April 2021. The samples were 76 subjects consisting of 38 premature infants (19 controls, 19 interventions) and 38 mothers (19 controls, 19 interventions) ethical clearance by the Health Research Ethics Committee of the Faculty of Medicine, Universitas Hasanuddin No. 938/UN4.6.4.5.51/PP36/2009. The results show 1) NIDCM is proven to be able to reduce maternal stress more compared to routine Developmental Care (DC); 2) NIDCM is proven to shorten the length of stay compared to routine DC in infants with a gestational age of ≥33 weeks with BW ≥1800 grams (Median : 1900 grams), while in infants with a gestational age of <33 weeks and BW <1800 grams (Median : 1650 grams), NIDCM and routine DC are not proven to shorten the length of stay. It can be concluded that applying NIDCM reduces the stressors felt by mothers while their infants are in the neonatal room. In addition, the condition of infants with birth weights less than 1800 grams needs special attention with NIDCM intervention.